The tamest of tigers? Understanding Hong Kong's innovation system and innovation policies. (23rd January 2006) - Sharif, Naubahar; Baark, Erik
Using Hong Kong as a case study, this paper explicates the innovation system in a 'Tiger' economy that has been less successful in making up lost technological ground than neighbouring Tiger economies. The paper outlines two important sides of Hong Kong's innovation system: its strengths, characterised by a focus on flexible linkages, learning patterns, absorptive capabilities and exploitation of existing technology; and its weaknesses, characterised by fragmentation in its current innovation policy mix, which has adversely affected its success in innovation-intensive fields. We argue that this policy mix needs urgent remediation if Hong Kong is to pull even in introducing technology and innovation policies.